Plant community assembly of alpine meadow at different altitudes in Northeast Qinghai‐Tibet Plateau - Minxia Liu; Lu Xu; Ruolan Mu; Guojuan Zhang; Ruixin Yu; Liang Li (Ecosphere, 2023)
Abstract The mechanism of community assembly is the core of ecological research. Using phylogenetic‐based and functional trait‐based methods jointly to explore the processes is a useful way to explain the change in assembly mechanisms. The present study combined these methods to explore the mechanism of plant community assembly in alpine meadows at different altitudes on the northeast Qinghai‐Tibet Plateau. We established a permanent study plot of 1.85 × 105 m2 and investigated 162 quadrats of 50 × 50 cm. We calculated the species richness, phylogenetic diversity (PD), standardized effect sizes PD (SES·PD), mean pairwise distance (SES·MPD), mean nearest taxon distance (SES·MNTD), and analyzed plant functional traits and phylogenetic signals. We found that the species richness and PD of plant community showed a “hump‐shaped” pattern, SES·PD showed a decreasing trend, and the phylogenetic structure changed from overdispersion (SES·MPD > 0, SES·MNTD > 0) to clustering (SES·MPD < 0, SES·MNTD < 0) with increasing altitude. The functional structure changed from overdispersion (nearest function index [NFI] < 0) to clustering (NFI > 0) with increasing altitude. Specific leaf area, leaf carbon content, and leaf phosphorus content had weak phylogenetic signals (K < 1, p < 0.05), and the other functional traits (plant height, leaf nitrogen content, leaf dry matter content, and relative chlorophyll content) did not show phylogenetic signals (K < 1, p > 0.05). The above results showed that competitive exclusion was the main driving force of community assembly at low altitudes (3000 and 3250 m), and habitat filtration was the main driving force of community assembly at high altitudes (4000 and 4500 m). For medium altitudes (3500 and 3750 m), the habitat was more complex because it was in the transition area between high and low altitudes, so the process of community construction may be random, habitat filtering, or competitive exclusion. On the whole, the niche process (deterministic process) was more important in driving for plant community assembly in the alpine meadow of the Qinghai‐Tibetan Plateau.